Internalisasi Nilai-Nilai PAI dalam Meningkatkan Pemahaman Moderasi Beragama di Sekolah Dasar - Afifudin Al Hadiq; Afinda Rahayu; Muhamad Akif Ardiyansah; Muhamad Nahrowy; Ulya Ziyanatuzzahro (Civiliza Publishing, 2023)
This study aims to explore the role of internalizing the values of Islamic Religious Education (PAI) in increasing understanding of religious moderation in elementary schools. Religious education has an important role in forming tolerance, mutual respect and interfaith harmony among students. In this study an analysis of the approaches and methods of Islamic education used in elementary schools was carried out. This discussion also highlights the importance of internalizing PAI values in building the moral and ethical foundations of students. Through good religious education, students are taught about universal values such as respect for human rights, social justice, and concern for the environment. This helps students develop a strong moral conscience and become responsible individuals in their religion. internalization of PAI values has a crucial role in increasing understanding of religious moderation in elementary schools. In this process, students develop an inclusive attitude, positive behavior, and a deep understanding of religion that is based on the values of tolerance, justice, and compassion. The results of this study provide important insights for educators and practitioners in designing an effective and impactful PAI learning approach in increasing understanding of religious moderation in elementary schools.